Assembly of the switch complex onto the MS ring complex of Salmonella typhimurium does not require any other flagellar proteins. - Kubori, T (1997)
The cytoplasmic portion of the bacterial flagellum is thought to consist of at least two structural components: a switch complex and an export apparatus. These components seem to assemble around the MS ring complex, which is the first flagellar basal body substructure and is located in the cytoplasmic membrane. In order to elucidate the process of assembly of cytoplasmic substructures, the membrane localization of each component of the switch complex (FliG, FliM, and FliN) in various nonflagellated mutants was examined by immunoblotting. It was found that all these switch proteins require the MS ring protein FliF to associate with the cell membrane. FliG does not require FliM and FliN for this association, but FliM and FliN associate cooperatively with the membrane only through FliG. Furthermore, all three switch proteins were detected in membranes isolated from fliE, fliH, fliI, fliJ, fliO, fliP, fliQ, fliR, flhA, flhB, and flgJ mutants, indicating that the switch complex assembles on the MS ring complex without any other flagellar proteins involved in the early stage of flagellar assembly. The relationship between the switch complex and the export apparatus is discussed.